Phenolic Content, Antioxidant and Hepatoprotective Activities of Sabah Hoya coronaria Blume - Muhammad Dawood Shah; Senty Vun-Sang; Mohammad Iqbal (Universiti Malaysia Sabah, 2023)
A common challenge that regularly results from oxidative stress is hepatic damage. This condition is characterised by a gradual progression from steatosis to chronic hepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma. The study proposed to assess the antioxidant activity and efficacy of Hoya coronaria aqueous extract in preventing CCl4-induced hepatic damage in rats. The DPPH technique was used in the study to assess the extract's antioxidant properties. The rats received dosages of 125 and 250 mg/kg body weight of H. coronaria extract for 14 days, followed by CCl4 exposure. After two weeks, the rats were euthanised for analysis. The results indicated that the extract showed significant antioxidant potential and decreased the impact of CCl4 on hepatic damage markers such as serum aspartate transaminase and alanine transaminase. Moreover, it increased hepatic reduced glutathione and various antioxidant enzymes while reducing malondialdehyde formation induced by CCl4. Additionally, the histopathological analysis demonstrated that H. coronaria extract protected the liver against fatty degeneration and necrosis induced by CCl4 toxicity. These outcomes suggest that H. coronaria extract could be used to prevent ROS-related hepatic damage.